SUTAINABLE FASHION: STYLE AND ETHIC - Munisa Nazirova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Sustainable fashion is considered to be a multifaceted approach to the consumption and production of clothing where there is a balance between style and ethics. This growing movement is responding to all requests and needs for more environmentally friendly and socially responsible practices in the fashion industry.